CONFERÊNCIA MAGNA - KEYNOTE SPEAKER - CONCITEC 2019 - Thompson, Maria (PontodeAcesso, 2020)
This paper constitutes an informal, direct narrative describing my lecture at the 2nd International Conference on Convergence in Information Science, Technology and Education (CONCITEC), Federal University of Bahia (UFBA), 26 to 28 September 2019. It was an honor and a joy to present at CONCITEC 2019 and to support the efforts of Professor Barbara Coelho, whom I was delighted to meet. The emphasis of my talk was in demonstrating that hard work, optimism and human connectivity can lead to amazing work and life experiences. I explained that I did not have special resources when I started my studies at UFES (Federal University of Espirito Santo), in Vitoria Brazil. I wanted to communicate to the audience that the obstacles and lack of resources, that they often experience in Brazil, while discouraging, should not prevent anyone to pursue their dreams. I particularly encouraged the women in the room, as it was very inspiring to me to see a group of strong women leading that forum